ANALISIS PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP OPINI AUDIT GOING CONCERN - Abdurrachman Abdurrachman; Rizky Amalia; Bryan Givan (FKIP, Universitas Banten Jaya, 2021)
Companies that receive a going concern audit opinion show events and conditions that would cause the auditor to doubt about the going concern of the company. This opinion can be used as an initial signal for users of financial statements to avoid mistakes when making a decision. Regarding the factors that influence going-concern audit opinion, many previous studies have been carried out. However, it has inconsistencies in the results of the study. Thus, the research aims to carry out retesting related